Synchronous multi-wavelength mode-locked laser at 2-μm based on Mamyshev cavity - Gong, Rui; Geng, Yalin; Pei, Li; Wei, Huai (Frontiers in Physics, 2023)
In recent years, 2-μm band lasers have developed rapidly due to their wide range of usage. It is a challenging problem to realize the synchronization of multi-wavelength multi-channel ultrashort pulses for many important applications. In this paper, a 2-μm synchronous multi-wavelength fiber laser is proposed. The laser was constructed based on cascaded Mamyshev regenerators. The multi-cascade nonlinear broadening and offset filtering can act as a saturable absorber, enabling mode locking, and resolving the issues of gain competition and synchronous output encountered in traditional multi-wavelength lasers. A stable synchronous multi-wavelength mode-locked laser was realized through numerical simulation. The laser can provide six-channel ultrashort pulses with a wavelength interval of 5 nm (the central wavelengths range from 2000 nm to 2025 nm). The peak power and duration of the output pulses are respectively 0.1~0.25 kW (intracavity peak power 0.4~1.1 kW for coupler ratio is 20:80) and ~1.1 ps. Design principles and the effects of various parameters such as the filter, the fiber length, etc on the optimization of the laser are analyzed and discussed.